2016
DOI: 10.3168/jds.2016-11032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fermentation and biohydrogenation intermediates in continuous cultures fed low and high levels of fat with increasing rates of starch degradability

Abstract: Excessive levels of starch in diets for lactating dairy cattle is a known risk factor for milk fat depression, but little is known about how this risk is affected by differences in rates of starch degradability (Kd) in the rumen. The objective of this study was to compare accumulation of biohydrogenation intermediates causing milk fat depression, including conjugated linoleic acid (CLA), when corn with low or high Kd were fed to continuous cultures. Diets contained (dry matter basis) 50% forage (alfalfa pellet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
4
30
4
1
Order By: Relevance
“…We did not assess the endosperm texture and the degree of grain processing (factors that affect the availability of starch to the animal), but the high concentration of starch stimulates the production of microbial protein in the rumen, increasing the production and concentration of milk protein Lascano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We did not assess the endosperm texture and the degree of grain processing (factors that affect the availability of starch to the animal), but the high concentration of starch stimulates the production of microbial protein in the rumen, increasing the production and concentration of milk protein Lascano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Specific to ALA, its proportion in milk was greatest when feeding GC + 3% FSO (Table 6). Lascano et al (2016) reported that the outflow of ALA either tended to increase when the starch degradability of corn grain varied from low to high or increased significantly when feeding soybean oil to fermentors during continuous culture. They also observed a reduction in ALA biohydrogenation with the increase in corn grain starch degradability (Lascano et al, 2016).…”
Section: Flaxseed Oil × Corn Grain Particle Size Interactionmentioning
confidence: 99%
“…In addition, Lascano et al (2016) reported elevated production of trans FA intermediates (e.g., trans-10 18:1, trans-10,cis-12 18:2) associated with milk fat depression when starch degradability was increased from low to high. Results from these 2 studies (Neveu et al, 2014;Lascano et al, 2016) suggest that further research is needed to better understand the potential interactions between oil and cereal grain PS on production and milk FA profile.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations